Book Reviews. Issue 1 (1st October 2013) - Martin, Kathi; Cecil, Anne; Golembuski, Cynthia
Shanghai Street Style, Toni Johnson-Woods and Vicki Karaminas with Photography by Fung Chan (2013) Bristol: Intellect, 168 pp., ISBN: 9781841505381, Paperback, £15.95, $25Shanghai Street Style, Toni Johnson-Woods and Vicki Karaminas with Photography by Fung Chan (2013) Bristol: Intellect, 168 pp., ISBN: 9781841505381, Paperback, £15.95, $25Why Would Anyone Wear That? Fascinating Fashion Facts, Celia E. Stall-Meadows with Illustrations by Leslie Stall Widener (2013) Bristol: Intellect Ltd., 83 pp., ISBN 9781841507279, Paperback, £9.95, $18,  €12